USING NUMBERED HEADS TOGETHER COOPERATIVE LEARNING AS SPEAKING STRATEGY - Panjaitan, Andre Bona Josua; Hasibuan, Ikhsan Ramadhan; Sembiring, Yenita (ELT (English Language Teaching Prima Journal), 2022)
This study aims to determine the students' ability to speak English with the classroom action research technique to change the model of student learning with the Numbered heads together method. The research is SMK Telkom 2 Medan class X, there are still many students who can't speak English and lack confidence in their abilities. We as researchers look for the problem points in these students and choose technical methods that make them active and can speak English. using the NHT method as a guide because students are more active in learning with groups, with this method the level of students' speaking ability is increasing. Before using this method only 25.7% of students' ability to understand it. While after using this method 70.33% of students' increase in student ability. from si This method is very active for students because students learn in groups more actively and so they get satisfactory results. This research has a special ability, namely changing the learning system of students who do not understand, uniting them with students who understand, and making them into competent teamwork. The problem that occurred during this lesson was because of the COVID-19 pandemic, students were learning online which made them a little constrained, but with the help of the school to study face-to-face, they became active in learning English. Keywords : English, technique, NHT, method, learning, and teamwork